2016
DOI: 10.1002/cnma.201600297
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Outer and Inner Nickel Particles in a Mesoporous Support: How the Channels Modify the Reducibility of Ni/SBA‐15 Catalysts

Abstract: Two different nickel supported on SBA‐15 catalytic systems have been prepared by means of impregnation (Ni/SBA‐15‐ImU) and deposition‐precipitation (Ni/SBA‐15‐DP) methodologies. Upon calcination, Ni/SBA‐15DP presents a well‐developed nickel phyllosilicate phase, which after reduction gives rise to a dispersed and homogeneous metallic phase, mainly located inside the 5 nm in diameter mesoporous structure of the support. On the contrary, as evidenced by XRD and a double temperature programmed reduction (TPR) pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
(33 reference statements)
3
16
0
Order By: Relevance
“…On the contrary, the TEM image of Co/SBA-15 ( Figure 5c) shows bigger heterogeneous particles with a mean diameter around 13-15 nm (Table 1) Figure 4 indicated that after this treatment most of metal should remain oxidized, the undetected oxidized nickel must be located inside the mesoporous channels in both catalysts, which are invisible for XPS, a surface sensitive technique. So, as found previously for different preparation methods [40], the deposition-precipitation methodology seems to favor the confinement of nickel inside the porous of SBA-15.…”
Section: Characterization Of Reduced Catalytic Systemssupporting
confidence: 77%
See 3 more Smart Citations
“…On the contrary, the TEM image of Co/SBA-15 ( Figure 5c) shows bigger heterogeneous particles with a mean diameter around 13-15 nm (Table 1) Figure 4 indicated that after this treatment most of metal should remain oxidized, the undetected oxidized nickel must be located inside the mesoporous channels in both catalysts, which are invisible for XPS, a surface sensitive technique. So, as found previously for different preparation methods [40], the deposition-precipitation methodology seems to favor the confinement of nickel inside the porous of SBA-15.…”
Section: Characterization Of Reduced Catalytic Systemssupporting
confidence: 77%
“…Despite this loss of surface area, the analysis by TEM (Figure 1) shows that the channeled structure of the SBA-15 support is preserved [35]. The calcined Ni x Co 1-x /SBA-15 catalysts present the characteristic "fibrous" structures of phyllosilicate phases, previously found in similar systems [36][37][38][39][40]. The ascription of these fibrous shapes to phyllosilicate is confirmed by the XRD diagrams included in Figure 2a.…”
Section: Characterization Of Fresh Calcined Systemssupporting
confidence: 62%
See 2 more Smart Citations
“…Simultaneously, the average pore size increases from 6.7 to 9-12 nm. Despite this loss of surface area and porosity, the images of the calcined catalysts obtained by TEM ( Figure 1) shows that the channeled structure of the SBA-15 support is preserved, with the "fibrous" structures of phyllosilicate phases generated during this treatment being visible [29][30][31]. The formation of (NiCo) 3 Si 2 O 5 (OH) 4 and/or (NiCo) 3 Si 4 O 10 (OH) 2 phyllosilicate phases [32] can be confirmed in the XRD diagrams of Figure 2 (left) by the wide peaks appearing around 35 and 61 o [33], the only phases detected in the calcined samples.…”
Section: Characterization Of Calcined and Reduced Catalystsmentioning
confidence: 99%